Simulation of the synergy of atmospheric emissions from the cement pole of the south coast of Paraíba on the city of Alhandra-PB (Research, Society and Development, 2022)
Atmospheric emissions of particulate matter (PM) and nitrogen oxides (NOx), typically emitted in the cement industry, have been generating great interest on the part of these industries in quantifying the air quality in the vicinity of their emission sources. Thus, the present work aims to simulate the synergy of atmospheric emissions from the cement factories located on the south coast of Paraíba over the city of Alhandra-PB, seeking to measure the amount of polluting load on the receiver, through modeling of the gaseous compounds emitted from the point source taken as the major contributor (clinker rotary blast furnace). For this purpose, the AID software (Instant Dispersion Assessment) based on the Gauss model was used to determine the concentrations in the air resulting from these emissions. In this determination, the main meteorological parameters from 2015 to 2016 and emission kinetics necessary for modeling were addressed. The maximum concentration of PM and NOx obtained after the modeling was respectively 0.0014 μg/m³ and 0.0027 μg/m³, being well below the primary and secondary air quality limits according to CONAMA 03/90. In the case evaluated, the estimated concentration does not present health risks to the exposed population, since, given the value obtained, it cannot be perceived.